Pendampingan Baca Kitab Cepat Desa Juwet Kenongo Porong Sidoarjo - Lutfianto; M Tohir (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
In studying religious knowledge, it cannot be denied that the absolute requirement is knowledge in Arabic, because the source of this religion is the Al-Qur'an and Hadith in Arabic. So it is very necessary to have a forum that can accommodate teenagers in Juwet village to be able to continue studying religion by starting with studying the rules of the Arabic language with the aim of being able to read and understand the meaning contained in the literature of Islamic study books. For this reason, training and assistance on how to read and then getting used to reading the Yellow Book properly and correctly needs to be applied. The target achievements of this program are the introduction of the yellow book for beginners, increasing the analysis of nahwu - shorof for the intermediate level, and increasing understanding and learning for the advanced level. This is very suitable for those who have an interest in the yellow book but do not have the opportunity to study at an Islamic boarding school. In this service, the main problem being worked on is how to improve the ability of teenagers in Juwet village, Kenongo in an effort to read the yellow book and pronounce Arabic sentences based on the study of Nahwu and Shorof Science. So, this training in reading the Kunig Book is a forum that can facilitate the teenagers of Pakong village to be able to continue their Islamic studies which were stopped when they entered junior high school or equivalent. From this community service activity, it can be concluded that it is intended to provide insight to the teenagers of Juwet village, Kenongo Porong Sidoarjo who are not yet familiar with the tradition of reading the yellow book or the bald book which is often a reference in religious community life. So that you can explore the meanings contained in it.